Impact of Personality Traits on Sustainable Entrepreneurship Development - Kathayat, Bhupal Bikram; Rawat, Dipak Singh; Gurung, Bablu (Journal of Innovation in Academia, 2023)
The evolving landscape of globalization is bringing about inevitable changes in the development of sustainable entrepreneurship. Sustainable entrepreneurship combines entrepreneurial traits with a focus on both market success and social impact. However, in today's competitive environment, it is imperative for every entrepreneur to possess specific personality traits to enhance their competitiveness. The primary objective of this research was to investigate the influence of four significant personality traits: agreeableness, openness, extraversion, and neuroticism, on the sustainable development of entrepreneurship in small and medium-sized enterprises (SMEs). The study employed a positivist research philosophy, an explanatory research design, and a quantitative survey method using a convenience sampling technique. A total of 396 entrepreneurs from the registered SMEs in the Surkhet district were identified as samples. Inferential statistics, specifically structural equation modeling, were used to analyze the data. The study revealed that personality traits such as agreeableness, openness, and extraversion had a positive influence on the development of sustainable entrepreneurship. This suggests that individuals possessing interpersonal skills, innovativeness, curiosity, situational sociability, confidence, and passion played a foundational role in promoting entrepreneurial sustainability. On the other hand, the personality trait of neuroticism demonstrated an insignificant positive impact on sustainable entrepreneurial development. This implies that neurotic individuals, prone to anxiety, stress, and emotional instability, may hinder decision-making processes and disrupt the stability of sustainable entrepreneurship. Based on these findings, the study suggests that entrepreneurs should prioritize instrumental features of personality traits like agreeableness, openness, and extraversion for sustainable entrepreneurship development, while minimizing the influence of neuroticism.